Exploring interactions of Aliivibrio fischeri with water-soluble polymers using bioluminescence and Raman microspectroscopy - Thomas J. Tewes; Britta Brands; Felix H. Schacher; Dirk P. Bockmühl (PLoS ONE, 2025)
Water-soluble polymers (WSPs) are widely used in biomedical and industrial applications. However, their ecological impact, including interactions with microorganisms, remains insufficiently understood and warrants further investigation. Aliivibrio fischeri, a bioluminescent bacterium, serves as a sensitive model to explore these effects. This study takes an exploratory approach, combining the optical spectroscopic techniques of luminescence measurements and Raman microspectroscopy to assess both immediate metabolic responses and potential longer-term or structural changes. Four WSPs polyacrylamide (PAM), polyethylene glycol (PEG), polyvinyl alcohol (PVOH), and polyvinylpyrrolidone (PVP) were each tested with three different molecular weights and five concentrations for luminescence measurements based on DIN EN ISO 11348. The tests revealed polymer-specific effects: PAM, PEG, and PVP suppressed luminescence, likely due to osmotic stress, adsorption, or viscosity-related limitations, with more pronounced inhibition observed at higher molecular weights. The strongest luminescence reduction was observed for PEG. Unlike the toxic reference substance 3,5-dichlorophenol (DCP), polymer-induced luminescence changes did not follow a consistent monotonic decay, suggesting that their effects are not solely attributable to acute toxicity. Notably, PVOH exposure increased luminescence, potentially reflecting stabilizing interactions or improved oxygen availability, which clearly contrasts with the suppressive trends observed for the other polymers. To investigate potential biochemical alterations, we applied Raman microspectroscopy to polymer-exposed A. fischeri. Partial least-squares discriminant analysis (PLS-DA) identified spectral differences, with polymer-specific patterns observed in regions commonly associated with membrane components, DNA, or carbohydrates. However, the PLS-DA coefficients primarily reflect statistical relevance and do not directly indicate specific biochemical mechanisms. These findings highlight spectral signatures relevant for classification, while biological interpretation requires further investigation. Our study provides exploratory insights into the potential impact of WSP exposure on bacterial metabolism and cellular composition, demonstrating the value of combining luminescence and Raman spectroscopy to detect polymer-related effects on microorganisms. While the observed spectral and metabolic changes suggest polymer-specific interactions, further research is needed to confirm the underlying mechanisms and assess their broader environmental and biotechnological implications.